Intertemporal Substitution and Labour Supply of Bosnian SME's - Ada Šabić-Lipovača; Wadim Strielkowski; Yuriy Bilan (Amfiteatru Economic Journal, 2016)
Our paper aims at testing the intertemporal substitution hypothesis (ISH) for small and medium enterprises (SMEs) in Bosnia and Herzegovina. The hypothesis predicts a positive relationship between the hours worked and the transitory changes in wages. We tested the hypothesis using the data on the daily income and worked hours collected via the survey questionnaire among small entrepreneurs in North-Western Bosnia and Herzegovina. The estimated wage elasticities turned out to be positive and different from zero, according to which it appears that the hypothesis of negative wage elasticities was not backed up by the empirical evidence. Our findings imply that the intertemporal labour substitution hypothesis found evidence and that we can reject the daily targeting hypothesis. We also argue that Bosnian entrepreneurs tend to pursue profits across working days because their main motive for running a business is the accumulation of capital and wealth, so that they follow the pattern of intertemporal labour substitution. The findings can be explained by an unfavourable business climate in Bosnia and Herzegovina, which is a result of a long-lasting transition process the country is still undergoing.
Keywords: C23; D90; J22; 330; labour supply; elasticity; intertemporal substitution; daily targeting; SMEs; Bosnia and Herzegovina